2004
DOI: 10.1016/j.physletb.2004.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling of valence neutrons from the core in 16C

Abstract: The neutron and proton excitations in 16 C nucleus have been investigated by use of the Coulomb-nuclear interference method applied to the 208 Pb + 16 C inelastic scattering. Angular distribution of the 16 C nuclei in the inelastic channel populating the first 2 + state has been measured. The neutron and proton transition matrix elements, M n and M p , have been determined from the "Coulomb" and "matter" deformation-length parameters obtained by distorted wave calculations. The M p or its corresponding B(E2; 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
35
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 12 publications
5
35
2
Order By: Relevance
“…A very quenched B(E2; 2 . This result combined with the deduced M n and M p values (from inelastic scattering of a 16 C beam on a 208 Pb target [2]) suggested a dramatic change in the nuclear structure of 16 C compared to the other even-even nuclei in its vicinity. Subsequent work * mpetri@ikp.tu-darmstadt.de [3] yielded a nuclear deformation parameter more in line with what is expected from the systematics, but when combined with the lifetime of Ref.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…A very quenched B(E2; 2 . This result combined with the deduced M n and M p values (from inelastic scattering of a 16 C beam on a 208 Pb target [2]) suggested a dramatic change in the nuclear structure of 16 C compared to the other even-even nuclei in its vicinity. Subsequent work * mpetri@ikp.tu-darmstadt.de [3] yielded a nuclear deformation parameter more in line with what is expected from the systematics, but when combined with the lifetime of Ref.…”
Section: Introductionmentioning
confidence: 72%
“…The even-mass neutron-rich carbon isotopes have been extensively studied recently [1][2][3][4][5][6][7] since quenched B(E2; 2 + 1 → 0 + 1 ) values and large asymmetries in the proton (M p ) and neutron (M n ) quadrupole matrix elements, M n /M p , were reported and interpreted as evidence of the decoupling of the valence neutrons from the core. In particular, 16 C was the first carbon isotope where such an interpretation was applied.…”
Section: Introductionmentioning
confidence: 99%
“…The topics discussed include, for example, the subshell closure of N=14 and N=16 and the anomalously small E2 transition strength observed in 16 C [1,2]. These issues are closely related to the competition of 0d 5/2 and 1s 1/2 neutron orbits.…”
Section: Introductionmentioning
confidence: 99%
“…It means that the hindrance of the B(E2; 2 16 C seems to contradict to the deformation expected from the E x (2 + 1 ). Moreover, the neutron and proton transition matrix elements, M n , M p derived from the 208 Pb+ 16 C inelastic scattering [3] imply that the neutron excitation is dominant in the 2 + 1 state of 16 C. From the point of view of collective deformations, these experimental results suggest the possible difference between proton and neutron shapes in 16 C. In the theoretical work on the proton-rich C isotopes [1], it was suggested that the difference of the shapes between proton and neutron densities may cause the suppression of B(E2). In the previous work [1], the difference between the proton and neutron shapes in the neutron-rich C isotopes was predicted as well as the proton-rich side.…”
Section: Introductionmentioning
confidence: 99%